Turbulent diffusion in a stably stratified shear layer - Chaudhry, Fazal Hussain, author; Meroney, Robert N., author; Fluid Dynamics and Diffusion Laboratory, Fluid Mechanics Program, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1969)
Diffusion of a passive substance released from a continuous point source in a stably stratified shear layer is investigated both theoretically and experimentally. Using Monin-Obukhov's velocity profile and assuming a vertical eddy diffusivity which is a power function of the stability parameter z/L, the Eulerian turbulent diffusion equation is solved to obtain expressions for vertical and longitudinal velocities of the center of mass of a cloud in the constant stress region. These expressions give physical substance to those suggested by Gifford (1962} and Cermak (1963} as intuitive extensions of Batchelor's Lagrangian similarity theory. The experimental investigation was made in the Army Micrometeorological Wind Tunnel at the Fluid Dynamics and Diffusion Laboratory of Colorado State University. The wind tunnel has a 6' x 6' x 80' test section. A stably stratified shear layer was produced by heating the air and cooling the wind tunnel floor. Detailed observations of the diffusion field, downwind ground and elevated point sources, have been made using Krypton-85 as a tracer. The concentration characteristics obtained from diffusion experiments show excellent agreement with those observed in the atmosphere. The data compares well with the predictions of similarity theory. It appears that the parameters evaluated in the field by Klug (1968) hold also for the wind tunnel data. The data support the assumption of a Gaussian effect of source height, for elevated releases, on the ground level concentration. An examination of the available solutions to the three dimensional diffusion equation as compared to the data suggests that the detailed diffusion patterns obtained from the wind tunnel experiments may be preferable over such solutions which require arbitrary specification of a lateral diffusivity.
Task IIB Research Technical Report Deseret Test Center.
TR ECOM-0423-5; Reports control symbol OSD-1366.
September 1969.
Keywords: Atmospheric turbulence; Diffusion